Ignoring Islamic Law for Family Harmony: The Practice of Delaying Inheritance Distribution in the Indigenous Muslim Community of Kampar, Riau - Deri Eka Putra; Riyanta, Riyanta (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2024)
The delay in inheritance distribution within the indigenous Muslim community of Kampar, Riau, is a longstanding tradition often justified as an effort to maintain family harmony. This phenomenon indicates that although Islamic inheritance law has been normatively established, its application is often selective or postponed in actual social practice. This study investigates the reasons behind such delays, the justifications provided by the community, and their implications for the understanding and implementation of Islamic law. This article use a qualitative approach, which data were collected through in-depth interviews toward religious and traditional leaders. The findings show that delay is not due to ignorance of Islamic legal obligations. Rather, it is a conscious decision rooted in cultural norms, socio-economic considerations, and emotional factors, such as respect for parents and the desire to avoid family conflict. This practice is supported by a communal consensus that prioritizes unity over immediate legal compliance. However, the study argues that although intended to preserve harmony, such postponements risk marginalizing rightful heirs and contradict the justice-oriented objectives of Islamic law (maqāṣid al-sharī’ah). The study concludes that contextual negotiation between customary traditions and Islamic law is necessary but must occur within a framework that ensures justice and legal clarity. Penundaan pembagian warisan dalam komunitas Muslim adat di Kampar, Riau, adalah tradisi yang telah berlangsung lama dan seringkali dibenarkan sebagai upaya untuk menjaga keharmonisan keluarga. Fenomena ini menunjukkan bahwa, meskipun hukum waris Islam telah ditetapkan secara normatif, ia seringkali diterapkan secara selektif atau tertunda dalam praktik sosial. Studi ini menyelidiki alasan penundaan tersebut, alasan yang diberikan oleh komunitas, dan efeknya terhadap pemahaman dan penerapan hukum Islam. Artikel ini menggunakan pendekatan kualitatif, yang datanya dikumpulkan melalui wawancara mendalam terhadap tokoh agama, dan tokoh adat. Temuan menunjukkan bahwa penundaan tidak disebabkan oleh ketidaktahuan tentang kewajiban hukum Islam. Sebaliknya, itu adalah pilihan yang dibuat secara sadar berdasarkan norma budaya, pertimbangan sosial ekonomi, dan faktor emosional, seperti penghormatan terhadap orang tua dan upaya untuk menghindari konflik keluarga. Konsensus masyarakat yang mengutamakan persatuan daripada pemenuhan hukum segera mendukung praktik ini. Namun, penelitian ini berpendapat bahwa, meskipun dimaksudkan untuk menjaga keharmonisan, penundaan tersebut berpotensi meminggirkan ahli waris yang berhak, yang bertentangan dengan tujuan keadilan hukum Islam (maqāṣid al-sharī’ah). Menurut penelitian ini, perundingan kontekstual antara adat dan hukum Islam perlu dilakukan, tetapi harus dilakukan dalam kerangka yang menjamin keadilan dan kejelasan hukum.